2006
DOI: 10.1590/s0074-02762006000900039
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic stereology of schistosomiasis mansoni infected-mice fed a high-fat diet

Abstract: High-fat diets induce weight gain and fatty liver in wild-type mice. Schistosomiasis mansoni infection also promotes hepatic injury. This study was designed to quantify hepatic alterations in schistosomiasis mansoni infected mice fed a high-fat diet (IHFC) or standard chow (ISC), uninfected mice fed a high-fat diet (HFC) or standard chow (SC). Mice were sacrificed during early infection (9 weeks from exposure). The following hepatic biometry and the stereology parameters were determined: volume density (hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 44 publications
2
27
0
1
Order By: Relevance
“…Although proved relevant in clinical studies (6), very little is known about stereological data in hepatic schistosomiasis (7,8). The diet of the host has been suggested to be a stimulation factor to hepatic regeneration (15).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although proved relevant in clinical studies (6), very little is known about stereological data in hepatic schistosomiasis (7,8). The diet of the host has been suggested to be a stimulation factor to hepatic regeneration (15).…”
Section: Discussionmentioning
confidence: 99%
“…The diet of the host has been suggested to be a stimulation factor to hepatic regeneration (15). Schistosomiasis also represents a stimulus during the acute phase of the infection (8,15). The present findings showed that both malnutrition and schistosomiasis led to adverse effects on liver morphology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations